2017
DOI: 10.1002/eqe.2973
|View full text |Cite
|
Sign up to set email alerts
|

Computational simulation of slab vibration and horizontal‐vertical coupling in a full‐scale test bed subjected to 3D shaking at E‐Defense

Abstract: Summary This paper focuses on slab vibration and a horizontal‐vertical coupling effect observed in a full‐scale 5‐story moment frame test bed building in 2 configurations: isolated with a hybrid combination of lead‐rubber bearings and cross‐linear (rolling) bearings, and fixed at the base. Median peak slab vibrations were amplified—relative to the peak vertical shake table accelerations—by factors ranging from 2 at the second floor to 7 at the roof, and horizontal floor accelerations were significantly amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, evidence was presented that vertical vibration characteristics and thus axial force variation in full-scale building is determined by flexibility of the floor slabs and not the vertical stiffness of the isolators. 25,26 Although many studies have demonstrated the effect of vertical or 3D shaking on increased base shear, no study has developed a general theoretical basis or simplified approach for accounting for such effects that can be implemented for design. Cilsalar and Constantinou 17 developed statistical results for the ratio of base shear with versus without vertical shaking, ranging from 1.06 to 1.22 for far-field motions and from 1.15 to 1.48 for near-fault motions.…”
Section: Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence was presented that vertical vibration characteristics and thus axial force variation in full-scale building is determined by flexibility of the floor slabs and not the vertical stiffness of the isolators. 25,26 Although many studies have demonstrated the effect of vertical or 3D shaking on increased base shear, no study has developed a general theoretical basis or simplified approach for accounting for such effects that can be implemented for design. Cilsalar and Constantinou 17 developed statistical results for the ratio of base shear with versus without vertical shaking, ranging from 1.06 to 1.22 for far-field motions and from 1.15 to 1.48 for near-fault motions.…”
Section: Noveltymentioning
confidence: 99%
“…Multiple references noted that bearing axial force histories were more difficult to replicate than other responses. However, evidence was presented that vertical vibration characteristics and thus axial force variation in full‐scale building is determined by flexibility of the floor slabs and not the vertical stiffness of the isolators 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that vertical vibration significantly amplifies the vertical acceleration response of the structure. Guzman et al [28] designed a bearing and applied to a steel frame structure to form a seismic isolated structure. It conducted shake table tests on it under coupled horizontal and vertical earthquake excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Shaking table tests have testified that rubber base isolation system could significantly amplify vertical accelerations [1]. Especially for the building under the near-fault (NF) vertical earthquakes, the structural and nonstructural damage was significant [2].…”
Section: Introductionmentioning
confidence: 99%